Probing the HIV Reverse-Transcriptase enzyme with novel bifunctional HIV-1 RT inhibitors of the general formula (NRTI)-spacer-(NNRTI) - Mohamed, Ebrahim (Department of Chemistry, 2024)
The high levels of resistance elicited by both nucleoside (NRTI) and non-nucleoside (NNRTI) reverse transcriptase inhibitors have prompted the design of double-drugs combining these two entities with the aim of addressing the emergence of resistance as well as searching for synergism between the two drug target sites on HIV reverse transcriptase (RT). The strategy involves combining two different inhibitors into a single chemical entity via a linker, with the aim of developing a mixed-site inhibitor combining the inhibitory actions of each drug. This thesis describes the rational drug-design and synthesis of nine bifunctional drugs combining a nucleos(t)ide and a non-nucleoside reverse transcriptase inhibitor linked via different non-cleavable spacers. The C-5 position of the nucleos(t)ide portion of the bifunctional was used for attachment of the spacer throughout. However, the site of attachment on the nonnucleoside drug varies according to the inhibitor type. Chapter Two describes the first series involving the synthesis of bifunctional HIV-drugs using d4U as the NRTI and UC-781 as the NNRTI. This resulted in two unthiated UC-781/d4U entities being synthesized in a convergent manner in 16 steps for the pentane-propyne target and 20 steps for the target bearing PEG-propyne units using Sonogashira coupling methodology as a key step. Chapter Three describes the second series incorporating a new NNRTI in the form of 2- and 4- pyrimidinylarylamine motifs. Key features in this chapter include the synthesis of tri-substituted anilines, the library generation of 2- and 4-pyrimidinylarylamine derivatives as model NNRTIs, as well as Sonogashira coupling reactions to obtain three bifunctional targets. The final part of this thesis describes the synthesis of a remarkable d4U/TMC120 bifunctional system, synthesized on the basis of molecular modeling. Biological results indicate that the d4U4-PEG-TMC120 bifunctional has the lowest EC50 anti-HIV activity of any NRTI-spacer-NNRTI bifunctional inhibitor synthesized to date. The NRTI was also triphosphorylated and the product evaluated in an in vitro RT inhibition assay, which culminated in a 'proof of principle' of synergy existing between the substrate site and the allosteric binding pocket. Also presented, is work carried out to change the rigid d4U to a more flexible acyclic nucleotide phosphonate in a pronucleotide approach. A range of conclusions on the work are presented at the end.